International drug policy – health before politics. Issue 2 (5th June 2017) - Ford, Chris; Saville, Sebastian
Abstract : Purpose: The purpose of this paper is to explain how international drug policy continues to have a hugely damaging effect on population health, human rights and wellbeing, not only on individuals who consume and/or sell drugs but also on societies as a whole. And to review whether anything has changed after United Nations General Assembly Special Session. Design/methodology/approach: UNGASS had been seen as a real opportunity for scientific evidence to become the driver of future drug policy. This paper looks at any changes that have since taken place that might support such an aspiration. Findings: The authors found the criminalisation and incarceration of people who use drugs, mainly from the most marginalised sections of society, remains the primary response in almost every member state of the UN and there are at least 33 countries that retain the death penalty for drug offences. The impact on the health of people who inject drugs (PWIDs) living with HIV is devastating and overdose and AIDS related mortality are the leading causes of death. Hepatitis C infections among PWIDs are increasing at epidemic levels even though this now a curable disease. Practical implications: Changes in drug policy urgently needed. Originality/value: This paper is an important review of the health implications of bad drug policy.